2018
DOI: 10.12998/wjcc.v6.i15.908
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of inflammatory bowel disease in a South Asian population

Abstract: AIMTo estimate prevalence and phenotypic associations of selected inflammatory bowel disease (IBD)-associated genetic variants among Sri Lankan patients.METHODSA case study of histologically confirmed ulcerative colitis (UC) or Crohn’s disease (CD) patients with ≥ 1 year disease duration, who were compared to unrelated, gender-matched, healthy individuals as controls, was conducted at four major centers in Sri Lanka. Phenotypic data of the cases were obtained and all participants were genotyped for 16 selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…A Sri Lankan case-control study published in 2018 concluded heterogenicity of allelic mutations in South Asian patients when compared to White patients [41]. Surprisingly, most SNPs and disease associations reported in this study have not been reported previously in South Asian populations.…”
Section: Genetic Determinants Of Inflammatory Bowel Disease In South ...contrasting
confidence: 68%
“…A Sri Lankan case-control study published in 2018 concluded heterogenicity of allelic mutations in South Asian patients when compared to White patients [41]. Surprisingly, most SNPs and disease associations reported in this study have not been reported previously in South Asian populations.…”
Section: Genetic Determinants Of Inflammatory Bowel Disease In South ...contrasting
confidence: 68%
“…Interestingly there is a very large difference in the disease associated allele frequency between populations: 45.6% in the Han-Chinese, 22% in South Asians and 2.5% for the Italian cohort. [9][10][11] The current study is valuable as it demonstrates the use of non-hypothesis driven approaches to identify genetic loci important in NASH. In addition to ATGL, several other proteins were found to interact with IFGGA2, and the following 5 may provide intriguing insights: i) cytochrome P450 monooxygenase (Cyp4a14) which catalyzes the hydroxylation of saturated carbon hydrogen bonds of fatty acids has a higher abundance in NAFLD, and adenovirus-mediated overexpression of CYP4A14 in livers of C57BL/6 mice induced steatosis.…”
mentioning
confidence: 99%
“…UGI tract involvement is more common in CD than in UC, and it is also known that it occurs more frequently in children than adults in CD ( 12 ). Recently, studies of CD report that South Asians have more UGI tract involvement than Westerners ( 13 ), which were explained by the genetic differences according to race and the influence of food culture ( 14 , 15 ). As an extension of these studies, emerging evidence suggested that UC also presents complications in the UGI tract ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%